Clinical characteristics and outcomes of patients with improvement in renal function during the treatment of decompensated heart failure - Testani, Jeffrey M. (2011)
BACKGROUND: In the setting of acute decompensated heart failure, worsening renal function (WRF) and improved renal function (IRF) have been associated with similar hemodynamic derangements and poor prognosis. Our aim was to further characterize IRF and its associated mortality risk. METHODS AND RESULTS: Consecutive patients with a discharge diagnosis of congestive heart failure at the Hospital of the University of Pennsylvania were reviewed. IRF was defined as a ≥20% improvement and WRF as a ≥20% deterioration in glomerular filtration rate. Overall, 903 patients met eligibility criteria, 31.4% experiencing IRF. Baseline venous congestion/right sided cardiac dysfunction was more common (p≤0.04) and volume of diuresis (p=0.003) was greater in patients with IRF. IRF was associated with a greater incidence of pre-admission (OR=4.2, 95% CI 2.6–6.7, p<0.0001) and post-discharge (OR=1.8, 95% CI 1.2–2.7 p=0.006) WRF. IRF was associated with increased mortality (adjusted HR=1.3, 95% CI 1.1–1.7, p=0.011), a finding largely restricted to patients with post-discharge recurrence of renal dysfunction (p interaction=0.038). CONCLUSION: IRF is associated with significantly worsened survival and may represent the resolution of venous congestion induced pre-admission WRF. Unlike WRF, the renal dysfunction in IRF patients occurs independent of the confounding effects of acute decongestion and may provide incremental information for the study of cardio-renal interactions.